2001
DOI: 10.1016/s0169-2070(00)00070-4
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarks and the accuracy of GARCH model estimation

Abstract: Reading's research outputs online 1 NOTICE: this is the author's version of a work that was accepted for publication in the International Journal of Forecasting. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in the International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(84 citation statements)
references
References 12 publications
(9 reference statements)
2
77
0
Order By: Relevance
“…As discussed in [69] and [20], there are several practical issues to consider in the maximization of (14). Starting values for the model parameters c, a i (i = 0, · · · , p) and b j (j = 1, · · · , q) need to be chosen and an initialization of 2 t and σ 2 t must be supplied.…”
Section: Estimation Of Garch Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed in [69] and [20], there are several practical issues to consider in the maximization of (14). Starting values for the model parameters c, a i (i = 0, · · · , p) and b j (j = 1, · · · , q) need to be chosen and an initialization of 2 t and σ 2 t must be supplied.…”
Section: Estimation Of Garch Modelsmentioning
confidence: 99%
“…EVIEWS, GAUSS, MATLAB, Ox, RATS, S-PLUS, TSP) and there are also a few free open source implementations. [41], [69], and [20] discussed numerical accuracy issues associated with maximizing the GARCH log-likelihood. They found that starting values, optimization algorithm choice, and use of analytic or numerical derivatives, and convergence criteria all influence the resulting numerical estimates of the GARCH parameters.…”
Section: Numerical Accuracy Of Garch Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Brooks et al [63] reviewed the most known software packages for estimation of ARCH models, and concluded that the estimation results differ considerably from one another. Table 2, in the Appendix, contains the ARCH models that have been presented in this section.…”
Section: { }mentioning
confidence: 99%